Coronary artery tortuosity and mid-term all-cause mortality of patients with ischemia and non-obstructive coronary arteries - Mihai Dumitru Emilian; Delcea Caterina; Buzea Cătălin Adrian; Balan Sabina; Dan Gheorghe Andrei (Sciendo, 2023)
Background: Coronary artery tortuosity (CAT) is a frequently encountered angiographic feature of patients with ischemia and non-obstructive coronary arteries (INOCA). However, there is limited data regarding the possible correlation between CAT and all-cause mortality in these patients.